Czech 23-month-olds use gender agreement to anticipate upcoming nouns - Smolík, Filip; Bláhová, Veronika (Journal of experimental child psychology, 2019)
Children acquiring Dutch, French, and Spanish can use gender of articles to facilitate the processing of upcoming nouns. The current study examined whether a similar effect can be found for bound gender-marking agreement morphemes in Czech, a language without obligatory articles. The experiment was designed so that the anticipatory effects of gender-marking morphemes before the head noun onset could be observed. In a preferential looking experiment, 33 children (aged 21-24 months) were shown picture pairs that could be labeled with masculine and feminine nouns. They heard a phrase comprising a demonstrative, an adjective, and a noun, where the first two elements were inflected for gender. The inflections were either correct (matching the noun gender) or incorrect (mismatched). Children were also given offline receptive grammar and vocabulary tasks. The group of children as a whole did not show significant differences in looking behavior between the experimental conditions. When split by the grammar task, the high-scoring children showed significant differences between looks toward the target noun in the matched and mismatched conditions even before the onset of the target noun. No significant difference was observed in the low-scoring group and in the groups split by vocabulary. Results suggest that knowledge of the gender system is just emerging before the second birthday and that more advanced children can use gender information encoded in bound morphemes to actively anticipate the upcoming nouns.
Keywords: genderová identita; Morphology; Female; Infant; předškolní dítě; Predictive language processing; ženské pohlaví; lingvistika; Language Development; lidé; jazyk (prostředek komunikace); Linguistics; Male; kojenec; Czech Republic; Gender Identity; Child, Preschool; Language acquisition; vývoj řeči; Language; Česká republika; Morphosyntax; Gender agreement; mužské pohlaví; Preferential looking; Vocabulary; slovní zásoba; Humans